PENGARUH KEPADATAN PADA SISTEM TRANSPORTASI BASAH TERTUTUP TERHADAP KELANGSUNGAN HIDUP BENIH IKAN PATIN SIAM (Pangasius hypophthalmus) UKURAN 3-5 CM - Rinohadi Kusuma Atmadja; Sri Oetami Madyowati; Achmad Kusyairi (Universitas Mataram, 2026)
Siamese catfish (Pangasius hypophthalmus) is one of the leading freshwater commodities and has high economic value in Indonesia. Increasing cultivation intensity to meetdomestic and export market demand has direct implications for the high demand for quality seeds. Closed wet transportation is an important part of aquaculture activities. This method has significant advantages in terms of logistics efficiency. This study aims to assess the effect of density on closed wet transportation systems on the survival of Siamese catfish (Pangasius hypophthalmus) seeds with a size of 3-5 cm. This study is expected to provide recommendations for the transportation of the density of Siamese catfish (Pangasius hypophthalmus) in size 3-5 cm. This study uses the analysis method of normality tests in spss, variety homogeneity tests, variety fingerprints and the smallest real difference (BNT). Treatment A = Fish density 100 fish/liter (0) (Control Treatment, Treatment B = 150 fish/liter, Treatment C = 200 fish/liter, Treatment D = 250 fish/liter. From the study, the most optimal density of Siamese catfish (Pangasius hypophthalmus) is the highest which is 200 fish/liter with an average SR of 98.08%. With water quality including: water temperature: 26.1 °C – 26.8 °C, water pH: 6.1 – 6.9 and Dissolved Oxygen (DO): 2.0 – 6.3 ppm.